1987
DOI: 10.1007/bf00217064
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned taste aversion induced in rats by intracerebral or systemic administration of monoamine oxidase inhibitors

Abstract: Conditioned taste aversion (CTA) elicited by systemic or intracerebral application of the monoamine oxidase inhibitors clorgyline (C), pargyline (P) or deprenyl (D) was studied in 402 rats. Water-deprived animals were allowed 15 min access to 0.1% sodium saccharin (CS) followed 10 min later by IP or by intracerebral injection of the drug. In the latter case, the animals were anesthetized 5 min after saccharin drinking with pentobarbital and the drug was stereotaxically injected (1 microliter/min, 1-2 microlite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…The lack of ICSS threshold-lowering effects of harmane, norharmane, and harmine contrasts with findings that some clinical MAO inhibitors (e.g., selegiline) can have addiction-like effects in other assays (e.g., place conditioning) in rats or mice (Porsolt et al, 1984;Wu and Zhu, 1999), although other studies reported no abuse potential or even aversive effects of clinical MAO inhibitors as measured using i.v. self-administration in rhesus monkeys (Winger et al, 1994) or conditioned taste aversion in rats (Buresova and Bures, 1987). Our data also contrast with a report that norharmane was reinforcing in an i.v.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of ICSS threshold-lowering effects of harmane, norharmane, and harmine contrasts with findings that some clinical MAO inhibitors (e.g., selegiline) can have addiction-like effects in other assays (e.g., place conditioning) in rats or mice (Porsolt et al, 1984;Wu and Zhu, 1999), although other studies reported no abuse potential or even aversive effects of clinical MAO inhibitors as measured using i.v. self-administration in rhesus monkeys (Winger et al, 1994) or conditioned taste aversion in rats (Buresova and Bures, 1987). Our data also contrast with a report that norharmane was reinforcing in an i.v.…”
Section: Discussioncontrasting
confidence: 99%
“…Collectively these results suggest that acute inhibition of the DRN via 5-HT 1A autoreceptors is rewarding, whereas stimulation of 5-HT 1A and 5-HT 1B heteroreceptors is aversive. This conclusion is consistent with pharmacological studies using acute administration of a serotonin-specific reuptake inhibitor or monoamine oxidase inhibitor to enhance 5-HT function, which rodents find aversive (Berendsen and Broekkamp, 1994; Buresova and Bures, 1987; Gommans et al , 1998; Prendergast et al , 1996) - but see (Olivier et al , 1999; Subhan et al , 2000). The idea of serotonin as an aversive signal has been further explored in “opponent process” theory (Boureau and Dayan, 2011; Cools et al , 2011; Daw et al , 2002).…”
Section: Influence Of 5-ht Autoreceptors On Behavior In Unstressedsupporting
confidence: 87%